A Growing Healthy, Ideal and Free of Anemia: Tumbuh Sehat, Ideal dan Bebas Anemia - Pratiwi, Rita Dwi; Ardi, Ni Bodro; Hasanah, Uswatun; Ismaya, Nurwulan Adi; Aulia, Gina; Indah, Fenita Purnama Sari; Fadhilah, Humaira; Fitriani, Dewi; Andriati, Riris; Hardianti, Tita (Ruang Ide Publisher, 2022)
Abstract A person's level of physical fitness can be seen from activities such as, students who take part in lecture activities need physical fitness to support the teaching and learning process on campus optimally. Physical examination which includes blood pressure, weight, height, waist circumference can be an indicator to determine physical fitness. Anemia also affects a person's nutritional status. The incidence of anemia in Indonesia is still quite high. Based on the Riskesdas 2018, it is stated that the prevalence of age 15-24 years in Indonesia is 32% anemia, meaning that 3-4 out of 10 teenagers suffer from anemia. The solution to overcome this problem was carried out by community service activities by lecturers and students at STIKes Widya Dharma Husada Tangerang with a target of 100 students. The implementation of this community service is carried out with the following methods: Blood pressure checks, weighing, measuring height, waist circumference, health counseling and giving Tablet Tambah Darah (TTD) for free to students. Most of the service participants do not know that anemia can occur in adolescents because of suboptimal nutritional intake and lack of physical activity so that participants are given health counseling to get education related to the knowledge of the importance of maintaining physical fitness for health and knowledge to prevent anemia. By holding this service activity, it is hoped that it can trigger the awareness of students to care more about health, routinely check health and assist government programs in reducing the incidence of anemia in the community. The follow-up to the results of this community service is that health checks, health counseling and the provision of Tablet Tambah Darah (TTD) can be carried out in different places so that more students understand the importance of health and can reduce the incidence of anemia. Keywords: Medical examination; Anemia; Tablet Tambah Darah